Smell and taste in titanium and nickel allergic sensitization in orthodontic patients. (4th May 2020) - Zigante, Martina; Peternel, Sandra; Muhvic Urek, Miranda; Rincic Mlinaric, Marijana; Pop Acev, Darko; Spalj, Stjepan
Abstract: Objective: To assess the prevalence of allergic sensitization to titanium and nickel in orthodontic patients and to evaluate alterations of smell and taste. Subjects and Methods: A total of 250 subjects were invited to participate, 245 accepted. The age range was 11‐45 years, 68% were females and 52% adolescents. An epicutaneous patch test was performed. Of the positive subjects in the patch test, 26 participated in the taste and smell testing and were matched by age and sex with 26 negative subjects. Results: The prevalence of hypersensitivity to titanium and/or nickel in orthodontic patients was 15.5%. Taste and smell were more impaired in sensitized subjects ( P ≤ .025), taste was more affected than smell and the tastes most affected were sour and bitter tastes, while the sweet taste was least impaired. Conclusion: The allergic sensitization to titanium is more uncommon than to nickel, with altered smell and taste related to those hypersensitivities.